Discrimination of Housing Rights of Certain Categories of Persons in Ukraine - Teremetskyi, V. I.; Теремецький, В. І.; Avramova, O. Ye. (Соціально-правові студії. - 2022. -Т. 5, № 3. - С. 52-59, 2022)
Визначено сутність та особливості житлової дискримінації як цивільно-правової категорії, виявлено її факти та підстави. Встановлено, що житлова дискримінація – це обмеження права на житло, внаслідок чого особа не має змоги придбати житло та стабільно в ньому проживати. З’ясовано, що найчастіше із житловою дискримінацією стикається вразлива група осіб (внутрішньо переміщені особи, сім’ї з дітьми, гомосексуальні пари тощо). Зазначено, що національне законодавство не виокремлює житлову дискримінацію як самостійну правову категорію. Охарактеризовано зміст та виявлено особливості житлової дискримінації в Україні. Розглянуто ознаки (стать, національність, громадянство, вік, сексуальна орієнтація, проживання сім’єю без реєстрації шлюбу, наявність дітей та тварин, внутрішнє переміщення), які стають причиною житлової дискримінації та неможливості реалізувати належне право на житло. Доведено, що дискримінація може виявлятися у відмові укласти чи продовжити договір оренди/найму, безпідставному підвищенні орендної плати тощо.

This paper is devoted to the problem of housing discrimination. The relevance of the study is conditioned, on the one hand, by the presence of facts indicating the existence of discriminatory phenomena in the housing sector, and on the other – by the lack of modern research on this issue. In addition, researchers have not yet established a stable terminology on discrimination issues and have not revealed the characteristic features of housing discrimination as a civil category. The solution of these problems is important both for further theoretical and legal developments in this area, and for bringing national legislation in line with international standards as soon as possible. The purpose of the study is to define the essence and features of housing discrimination as a civil category, identify its facts and grounds. The research material includes statistical data on the number and situation of vulnerable persons in the housing sector in Ukraine, facts of discrimination in Ukrainian society; scientific publications on housing rights and housing discrimination; report of the Commissioner for Human Rights in Ukraine for 2020; national legislation; statistics of internally displaced persons in 2022, etc. The materials and objectives of the study determined the choice of research methods. The primary method is axiological, which allows substantiating the value of housing for a person. Methods of analysis and synthesis helped identify general approaches to the concept of discrimination, characterise its grounds, and formulate a definition of housing discrimination. It is established that housing discrimination is a restriction of the right to housing, as a result of which a person does not have the opportunity to purchase housing and live in it. It was found out that most often a vulnerable group of people (internally displaced persons, families with children, homosexual couples, etc.) face housing discrimination. It is noted that national legislation does not distinguish housing discrimination as an independent legal category. The paper describes the content and features of housing discrimination in Ukraine. The characteristics (gender, nationality, citizenship, age, sexual orientation, family residence without marriage registration, the presence of children and animals, internal displacement) that cause housing discrimination and inability to exercise the proper right to housing are established. It is proved that discrimination can manifest itself in refusal to conclude or extend a lease/rental agreement, unjustified rent increases, etc. The paper can be used for further scientific study by young researchers dealing with the problems of improving housing legislation.

Определены сущность и особенности жилищной дискриминации как гражданско-правовой категории, выявлены ее факты и основания. Установлено, что жилищная дискриминация – это ограничение права на жилье, в результате чего лицо не имеет возможности приобрести жилье и стабильно в нем проживать. Выяснено, что чаще всего с жилищной дискриминацией сталкивается уязвимая группа лиц (внутренне перемещенные лица, семьи с детьми, гомосексуальные пары и т.п.). Отмечено, что национальное законодательство не выделяет жилищную дискриминацию как самостоятельную правовую категорию. Охарактеризованы содержание и выявлены особенности жилищной дискриминации в Украине.
Дискримінація житлових прав окремих категорій осіб в Україні
Keywords: дискримінація; житло; право на житло; обмеження; уразливі особи; житлова дискримінація; права людини; discrimination; housing; right to housing; restrictions; vulnerable persons; housing discrimination; human rights; дискриминация; жилье; право на жилье; ограничения; уязвимые лица; жилищная дискриминация; права человека